Comparison of cerebrovascular reactivity recovery following high‐intensity interval training and moderate‐intensity continuous training. Issue 11 (7th June 2020) - Burma, Joel S.; Macaulay, Alannah; Copeland, Paige; Khatra, Omeet; Bouliane, Kevin J.; Smirl, Jonathan D.
Abstract: A common inclusion criterion when assessing cerebrovascular (CVR) metrics is for individuals to abstain from exercise for 12–24 hr prior to data collections. While several studies have examined CVR during exercise, the literature describing CVR throughout post‐exercise recovery is sparse. The current investigation examined CVR measurements in nine participants (seven male) before and for 8 hr following three conditions: 45‐min moderate‐continuous exercise (at ~50% heart‐rate reserve), 25‐min high‐intensity intervals (ten, one‐minute intervals at ~85% heart‐rate reserve), and a control day (30‐min quiet rest). The hypercapnic (40–60 mmHg) and hypocapnic (25–40 mmHg) slopes were assessed via a modified rebreathing technique and controlled stepwise hyperventilation, respectively. All testing was initiated at 8:00a.m. with transcranial Doppler ultrasound measurements to index cerebral blood velocity performed prior to the condition (pre) with serial follow‐ups at zero, one, two, four, six, and eight hours within the middle and posterior cerebral artery (MCA, PCA). Absolute and relative MCA and PCA hypercapnic slopes were attenuated following high‐intensity intervals at hours zero and one ( all p <  .02). No alterations were observed in either hypocapnic or hypercapnic slopes following the control or moderate‐continuous exercise ( all p >  .13), aside from a reduced relative hypercapnic MCA slope at hours zero and one following moderate‐continuous exercise ( all p <  .005). The current findings indicate the common inclusion criteria of a 12–24 hr time restriction on exercise can be reduced to two hours when performing CVR measures. Furthermore, the consistent nature of the CVR indices throughout the control day indicate reproducible testing sessions can be made between 8:00a.m. and 7:00p.m. Abstract : Absolute and relative MCA and PCA cerebrovascular reactivity hypercapnic slopes were attenuated following high‐intensity intervals at hours zero and one (all p  < .02). No alterations were observed in either hypocapnic or hypercapnic slopes following the control or moderate‐continuous exercise (all p  > .13), aside from a reduced relative hypercapnic MCA slope at hours zero and one following moderate‐continuous exercise (all p  < .005). The current findings indicate the common inclusion criteria of a 12–24 hr time restriction on exercise can be reduced to two hours when performing CVR measures.